(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The interpretive approach employed in the current study seeks to reveal the contents of the Qur’anic discourse petinent to the descendants of Noah - peace be upon Him – and the Flood, because these two topics received a great deal of focus in the Qur’anic contexts. Howevr, most of the interpretations related to these topics were influenced by the literature of the People of the Book due to the presence of Noah’s story with them. Hence, we find a clear gap between the intentional significance of the Quranic discourse and the common tradition surrounding their events, and this matter was a great motivator to find an interpretation that is compatible with all Qur’anic contexts and that does not overlook any evidence of them.